Rectal diverticulitis mimicking rectal carcinoma with intestinal obstruction: Case report - Özçelik, Ümit; Bircan, Hüseyin Yüce; Eren, Eryiğit; Demiralay, Ebru; Işıklar, İclal and Demirağ, Alp and Moray, Gökhan (Turkish Journal of Gastroenterology, 2015)
Abstract Although diverticular disease of the colon is common, the occurrence of rectal diverticula is extremely rare with only sporadic reports in the literature since 1911. Symptomatic rectal diverticula are seen even less frequently, and surgical intervention is needed for only complicated cases. Here we report the case of a 63-year-old woman presenting with rectal diverticulitis mimicking rectal carcinoma with intestinal obstruction.